2014
DOI: 10.1071/cp13337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of banded ammonia and urea fertiliser on soil properties and the growth and yield of wheat

Abstract: Experiments conducted over three seasons in southern New South Wales tested the effects of concentrating anhydrous ammonia (AA) and urea fertiliser in bands occupying ~3.5% of the topsoil volume. Yield responses to applied nitrogen (N) were small or negative in a drought but larger (17 kg grain kg–1 N fertiliser) in favourable seasons. There was no consistent difference between AA and urea effects on yield, grain protein or efficiency of fertiliser-N recovery, and there were no consistent differences arising f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…Significant increase in sorghum biomass yield by N fertilization was due to increased photosynthesis and cell growth, which, in turn, results in accumulation of metabolites and thus increase biomass yield. Similar results were reported on crop yield increase by N fertilization without any significant differences between N sources (Olson et al 1986;Alcoz et al 1993;Angus et al 2014). The positive effects of deeper N injection (at 20 cm depth) on forage sorghum yields were due to greater N availability to crops with high moisture content, lower temperature, and partial anaerobic condition at deeper soil depth, compared to shallow and surface depths, respectively (USEPA 1998).…”
Section: Resultssupporting
confidence: 85%
“…Significant increase in sorghum biomass yield by N fertilization was due to increased photosynthesis and cell growth, which, in turn, results in accumulation of metabolites and thus increase biomass yield. Similar results were reported on crop yield increase by N fertilization without any significant differences between N sources (Olson et al 1986;Alcoz et al 1993;Angus et al 2014). The positive effects of deeper N injection (at 20 cm depth) on forage sorghum yields were due to greater N availability to crops with high moisture content, lower temperature, and partial anaerobic condition at deeper soil depth, compared to shallow and surface depths, respectively (USEPA 1998).…”
Section: Resultssupporting
confidence: 85%
“…However, for wheat that preferentially uses NO 3 − instead of NH 4 + as the main N source, an increase in NH 4 + uptake may not be beneficial to the plant when the ion is applied to the soil (Angus et al. ).…”
Section: Traits Influencing N‐uptake Efficiencymentioning
confidence: 99%
“…It will also be necessary to evaluate the contribution of direct NH 4 + uptake to the wheat N economy, as the available information on the NH 4 + transport systems at both the molecular and physiological levels remains fragmentary in wheat (Causin andBarneix 1993, Søgaard et al 2009) and in other cereals such as maize ) and rice (Gaur et al 2012). However, for wheat that preferentially uses NO 3 À instead of NH 4 + as the main N source, an increase in NH 4 + uptake may not be beneficial to the plant when the ion is applied to the soil (Angus et al 2014).…”
Section: Root N Transporter Systemsmentioning
confidence: 99%
“…The FRZ is the region around the initial point location of the fertilizer that is radically influenced by the chemistry of the soil (Singh, 1971; Heaney, 2001). Field studies have demonstrated that the banding of fertilizer at planting can have effect on stand establishment (Mason, 1971; Johnston et al, 2001; Grant et al, 2010; Angus et al, 2014) and crop yield (Angus et al, 2014).…”
mentioning
confidence: 99%
“…Controlling the rate and the source of the fertilizer being applied has been shown to mitigate the effects of the toxicity (Creamer and Fox, 1980; Passioura and Wetselaar 1972; Pan et al, 2016). A number of different N sources have been used in toxicity experiments, including anhydrous ammonia, urea ammonium nitrate (UAN), urea, di‐ammonium phosphate, mono‐ammonium phosphate, and ammonium sulfate (AS) (Passioura and Wetselaar, 1972; Creamer and Fox, 1980; Abbès et al, 1995; Kosegarten et al, 1997; Dowling, 1998; Coskun et al, 2013, Angus et al, 2014). These sources have been shown to have different effects on roots and the formation of the FRZ.…”
mentioning
confidence: 99%